Phosphatidylethanolamine Deficiency in Mammalian Mitochondria Impairs Oxidative Phosphorylation and Alters Mitochondrial Morphology - Tasseva, Guergana (American Society for Biochemistry and Molecular Biology, 2013)
Mitochondrial dysfunction is implicated in neurodegenerative, cardiovascular, and metabolic disorders, but the role of phospholipids, particularly the nonbilayer-forming lipid phosphatidylethanolamine (PE), in mitochondrial function is poorly understood. Elimination of mitochondrial PE (mtPE) synthesis via phosphatidylserine decarboxylase in mice profoundly alters mitochondrial morphology and is embryonic lethal (Steenbergen, R., Nanowski, T. S., Beigneux, A., Kulinski, A., Young, S. G., and Vance, J. E. (2005) J. Biol. Chem. 280, 40032–40040). We now report that moderate <30% depletion of mtPE alters mitochondrial morphology and function and impairs cell growth. Acute reduction of mtPE by RNAi silencing of phosphatidylserine decarboxylase and chronic reduction of mtPE in PSB-2 cells that have only 5% of normal phosphatidylserine synthesis decreased respiratory capacity, ATP production, and activities of electron transport chain complexes (C) I and CIV but not CV. Blue native-PAGE analysis revealed defects in the organization of CI and CIV into supercomplexes in PE-deficient mitochondria, correlated with reduced amounts of CI and CIV proteins. Thus, mtPE deficiency impairs formation and/or membrane integration of respiratory supercomplexes. Despite normal or increased levels of mitochondrial fusion proteins in mtPE-deficient cells, and no reduction in mitochondrial membrane potential, mitochondria were extensively fragmented, and mitochondrial ultrastructure was grossly aberrant. In general, chronic reduction of mtPE caused more pronounced mitochondrial defects than did acute mtPE depletion. The functional and morphological changes in PSB-2 cells were largely reversed by normalization of mtPE content by supplementation with lyso-PE, a mtPE precursor. These studies demonstrate that even a modest reduction of mtPE in mammalian cells profoundly alters mitochondrial functions.